Secondary woody vegetation patterns in New Zealand's South Island dryland zone - Susan Walker; Nigel King; Adrian Monks; Sophie Williams; Larry Burrows; Ellen Cieraad; Colin Meurk; Jacob McC Overton; Robbie Price; Mark Smale (New Zealand Journal of Botany, 2009)
Can New Zealand's indigenous dryland ecosystems be rehabilitated by facilitating inherent successional tendencies to enhance development of indigenous‐dominated and often woody communities in the long term? Here, we describe the geographic distribution of woody communities of New Zealand's South Island drylands to generate hypotheses about successional trajectories to future vegetation states. Presences and absences of woody species in 3880 vegetation plots collated from past surveys were used to predict species potential distributions across drylands. Separate models and spatial predictions were built for each of four classes of woody richness, which were used as surrogates for successional stages. Woody species richness increased significantly from grassland to shrubland and from shrubland to forest cover, and trends in species traits also suggest richness class was related with successional stage. Indigenous woody species outnumbered exotic species in all richness classes. Assuming richness classes represent temporal progressions, our results suggest relatively homogeneous early‐successional woody associations succeed to a divergent array of woody associations in different environments. Growth forms of species in our predicted associations suggest transitions from grassland to tall, tree‐rich forests in northern and coastal drylands, and to liane‐rich open or lightcanopied shrubland, woodland, or low forest in more severe inland environments. These putative communities are novel in species composition but physiognomically broadly similar to pre‐settlement analogues. Especially in severe inland environments, unassisted transitions from grassland to indigenousdominated late‐successional woody communities may depend on the exclusion of tall exotic trees, Scotch broom, and gorse in early succession.